PENGARUH POLITICAL CONNECTION DAN STRUKTUR KEPEMILIKAN TERHADAP FINANCIAL PERFORMANCE - Mursalim, Stella; Lukman, Hendro (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to empirically examine the effect of Political Connection (PC), Family Ownership (FO), and Managerial Ownership (MO) on Financial Performance in Infrastructure Companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The data used are 13 companies with 52 data. The test method used in this study is logistic regression using SPSS 20 software. Based on the results of the research that has been done, it means that Political Connection, Family Ownership, and Managerial Ownership have no effect on Financial Performance. The implication of this study for political connections who are competent in the field of business concerned and that family ownership and managerial ownership can work together in improving financial performance.